Genotypic and phenotypic characterization of rare globin variants in Northern Guangxi, China - Yang, Wei-Jia; Kang, Qing-Ping; Liang, Li-Ming; Zhou, Qian; Gong, Xiao-Min; Dou, Min; Huang, Cui-Juan; Lin, Ying (Frontiers in Immunology, 2025)
ObjectiveThe aim of this study is to examine the relationship between hematological parameters, hemoglobin electrophoresis findings, and phenotypic characteristics in individuals carrying rare thalassemia gene variants in Northern Guangxi, China.MethodsPeripheral blood samples were collected from 3,890 individuals (including 834 couples) who tested positive for thalassemia at the Prenatal Diagnosis Center of Guilin People’s Hospital between March 2019 and March 2025. Standard thalassemia genotyping was performed using Gap-PCR and PCR-reverse dot blot (PCR-RDB) assays to detect common α- and β-thalassemia mutations prevalent in southern China. Participants with negative results genotype-phenotype discordance underwent extended molecular testing to detect rare thalassemia variants. In cases where both partners were identified as carriers, amniotic fluid samples were collected from pregnant women for prenatal diagnosis.ResultsThalassemia major was diagnosed in 13 fetuses, with elective termination of two affected pregnancies. The detection rate for common thalassemia mutations was 44.27% (1,722/3,890), while rare variants were identified in 1.72% (67/3,890). Among participants with negative results from conventional genotyping, the detection rate of rare mutations increased to 26.38% (67/254). A total of 42 rare thalassemia variants were found, including 25 α-thalassemia, 14 β-thalassemia, and 3 δ-thalassemia mutations. A novel 4.3 kb deletion (chr16:176935–181274DEL), encompassing the α1 gene and a recombined non-functional gene-X-Y-Z segment, was reported for the first time. The -α4.3/–SEA genotype was associated with HbH disease.ConclusionA substantial frequency of rare thalassemia gene mutations was identified in the Northern Guangxi population, contributing to the regional mutational landscape. These rare genotypes were associated with distinctive hematological and hemoglobin electrophoretic features. Characteristic phenotypic patterns, combined with specific laboratory parameters, facilitated preliminary inference of genotypes and supported the application of targeted diagnostic approaches. This strategy may improve diagnostic accuracy, reduce missed or incorrect diagnoses, and enhance prenatal and postnatal management strategies.